The Practices Area at the University: news about a case (Praxis Educativa, 2014)
The new syllabuses at Facultad de Ciencias Humanas UNLPam (2009) prescribe a Practice Area for the teachers’ training. This is a new space added to the historical ones: General Training; Disciplinary Training and Teacher Training. The practices understood in this way are pointed towards systematic learning of capacities to act as teachers at school in the classrooms. This proposal supposes an important change regarding the way of understanding training and curriculum that gives place to a political project and a new kind of teaching that is generated with this particular way of training. In this paper we concentrate on the meaning and sense of a training that considers the formative value of practice in cooperative work among teachers of disciplinary and pedagogic areas that start to see the school as reference context in teaching action, the organization ways that are being activated and the action research that analyzes and studies thoroughly these political and curricular innovations.
Keywords: Practice Area; context; teaching actions; professionalism